Pengaruh Brand Experience terhadap Brand Loyalty dengan Brand Attachment sebagai Variabel Mediasi (Studi pada Pengguna iPhone di Kota Denpasar) - Utami, Ni Wayan Melia Dwi; Jatra, I Made (Universitas Pahlawan Tuanku Tambusai, 2024)
Smartphones are one of the tools that cannot be separated from human life today. Various smartphone brands are offered in the market, one of which is the iPhone brand smartphone which is known to have a higher price than other smartphone brands. This study aims to examine the effect of brand experience on brand loyalty through brand attachment for iPhone users in Denpasar City. This study used purposive sampling technique with a total sample size of 100 people. Data collection in this study using a questionnaire. The data analysis technique uses path analysis and sobel test. The results showed that brand experience and brand attachment have a positive and significant effect on brand loyalty, brand experience affects brand attachment, and brand attachment is able to partially mediate the effect of brand experience on brand loyalty. The theoretical implications of this study have been able to explain the theory of planned behavior and add to empirical studies and confirm the influence of brand attachment in mediating the effect of brand experience on brand loyalty. Suggestions that can be given to the management of the Apple Inc. company in order to continue to innovate, pay more attention and maintain a good brand experience provided to its users so that it can encourage brand attachment and increase brand loyalty for iPhone users in Denpasar City.